Current management of hypertension in general practice. Issue 6074 (4th June 1977) - Heller, R F; Rose, G
Abstract : An examination of the notes of 697 patients in a random sample of seven general practices in one part of inner London showed that 164 (24%) of 669 had had a blood-pressure recording in a five-year period. Proportions varied between 4% and 36% in the different practices. The blood pressure was raised (systolic greater than or equal to 160 mm Hg or diastolic greater than or equal to 100 mm Hg or both) in 74 patients (45%) whose blood pressure had been recorded, and another recording had subsequently been made in 45 (61%) of these patients. Fifteen (21%) of those with hypertension had not had a blood-pressure recording during the five years before the study. Tranquillisers or sedatives were the commonest drugs used in the treatment of hypertension. As in a study of the management of hypertension in hospital, opportunities provided by visits to the general practitioner were not commonly used for blood-pressure screening, and the discovery of hypertension often did not lead to further action.